2019
DOI: 10.1159/000502953
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Blocks Interleukin-13-Induced Intestinal Epithelial Barrier Dysfunction

Abstract: Introduction: Impaired intestinal epithelial barrier function is a hallmark of a variety of pathological conditions such as inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS). IBD patients with IBS-like symptoms show higher interleukin-13 (IL-13) serum levels and poor psychological well-being. Supplementary glutamine reduced the daily bowel movement frequency, improved the stool form, and normalized intestinal hyperpermeability. This study was aimed at assessing the effects of IL-13 and supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
0
14
0
1
Order By: Relevance
“…It is reported that addition of glutamine increased the expression of ZO-1 and occludin in methotrexate-treated Caco-2 cells (Beutheu et al, 2013). Glutamine increased the claudin-1 expression to reduce IL-13-induced barrier dysfunction (Li et al, 2019). In stressed humans, glutamine is known to regulate the expression of tight junction proteins and cellular localization in Caco-2 cell monolayers to maintain the intestinal barrier function (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that addition of glutamine increased the expression of ZO-1 and occludin in methotrexate-treated Caco-2 cells (Beutheu et al, 2013). Glutamine increased the claudin-1 expression to reduce IL-13-induced barrier dysfunction (Li et al, 2019). In stressed humans, glutamine is known to regulate the expression of tight junction proteins and cellular localization in Caco-2 cell monolayers to maintain the intestinal barrier function (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This improvement is associated with the restoration of the altered distribution of occludin and ZO-1 [69]. A recent study shows that pre-treatment with glutamine in vitro blocks the interleukin-13-induced intestinal epithelial barrier dysfunction characterized by a decrease of TEER and an increase of 4 KDa dextran permeability [70]. Glutamine deprivation not only affects the expression of tight junction proteins, but also reversely suppresses epithelial cell proliferation as shown in intestinal organoid cell culture [71].…”
Section: Glutaminementioning
confidence: 93%
“…Gln regulated TJ integrity and distribution through calcium/calmodulin-dependent kinase 2 (CaMKK2)-AMP-activated protein kinase signaling in porcine epithelial cells (111). Recently, Gln alleviated IL-13-induced barrier dysfunction by increasing CLDN-1 expression, via disruption of the phosphatidylinositol-3-kinase/Akt signaling pathway (112).…”
Section: Amino Acidsmentioning
confidence: 99%